Theoretical study of the CO formation mechanism in the CO2 gasification of lignite. (1st January 2018) - Li, Guang-Yue; Li, An-Qi; Zhang, Hang; Wang, Jie-Ping; Chen, Shi-Yun; Liang, Ying-Hua
Graphical abstract: Highlights: CO-formation mechanism in the CO2 gasification of lignite are simulated by ReaxFF. The ReaxFF simulation results well agree with previous experimental results. Chain carbon radicals produce CO with oxidized carbon radicals as intermediates. Elementary reactions in CO formation pathways are entropy-increasing. Abstract: Reactive force field (ReaxFF) molecular dynamics simulations of lignite and lignite-CO2 models were performed to investigate the CO formation mechanism of CO2 gasification process of lignite. A C++ program was developed to assess ReaxFF trajectories and to analyze elementary reactions involved in the mechanism. Calculated product distribution and relative amounts of main gas products show good agreement with reported experimental observations. We found that the CO formation pathways in the CO2 gasification of lignite begin with the chain carbon radical (Rn ), which is formed by CH/CC bond cleavage reactions of aromatic moieties in the lignite or produced semicoke at high temperatures. These chain carbon radicals can react with CO2, forming oxidized carbon radicals, such as Rn -O-C-O, Rn -CO2 and Rn -O. Among these radicals, Rn -O and Rn -O-C-O are important precursors of CO. They produce CO molecules by releasing their C-O moieties at the end. The thermodynamic properties of these elementary reactions were obtained by density functional theory calculations at the B3LYP/6-311 + G(2d, 2p) level. The calculated overall enthalpy and entropy changes could clearly explain the experimental data. The density functional theory results show that most of these elementary reactions are endothermic and entropy increasing. High gasification temperatures are favorable for the reactions.